2023
DOI: 10.1186/s12885-023-11140-6
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cohort study on changes in breast, lung and colorectal cancer incidence and mortality among non-Western immigrant women

Abstract: Background Cancer risk varies geographically, and migrants are influenced by different risk factors before, during and after migration. Increased migration from non-Western countries to the Nordic countries calls for a better understanding of the migrants’ cancer risk and the change in risk patterns over time. The aim of this study was to compare the incidence and mortality of breast, colorectal and lung cancer between non-Western immigrant and the native female population in Denmark, Finland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous research has indicated that immigrants, particularly non-Western individuals, exhibit a lower baseline risk of cancer, including cervical, colorectal and breast cancer [ 32 , 33 ]. However, this risk tends to align with that of the host population over time spent in the new country [ 34 ], although the exact length of stay was not available in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that immigrants, particularly non-Western individuals, exhibit a lower baseline risk of cancer, including cervical, colorectal and breast cancer [ 32 , 33 ]. However, this risk tends to align with that of the host population over time spent in the new country [ 34 ], although the exact length of stay was not available in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Lamminmäki et al (2023) reported that non-Western immigrant women in Nordic countries, Denmark, Finland, Iceland and Norway, had statistically significantly lower BC incidence than native women, but the BCR among immigrant women increased with the duration of residence [193]. Interestingly, these authors specified that higher education increased the BCR among immigrant women [193]. Similarly, BC rates of occurrence are four-seven times greater in America than in China and Japan.…”
Section: Migration Patterns and Breast Cancer Disparitiesmentioning
confidence: 99%
“…Migrants are influenced by different risk factors before, during and after migration [193]. Lamminmäki et al (2023) reported that non-Western immigrant women in Nordic countries, Denmark, Finland, Iceland and Norway, had statistically significantly lower BC incidence than native women, but the BCR among immigrant women increased with the duration of residence [193]. Interestingly, these authors specified that higher education increased the BCR among immigrant women [193].…”
Section: Migration Patterns and Breast Cancer Disparitiesmentioning
confidence: 99%